If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying x + -1(5x + -2) = 7(x + -1) + -2 Reorder the terms: x + -1(-2 + 5x) = 7(x + -1) + -2 x + (-2 * -1 + 5x * -1) = 7(x + -1) + -2 x + (2 + -5x) = 7(x + -1) + -2 Reorder the terms: 2 + x + -5x = 7(x + -1) + -2 Combine like terms: x + -5x = -4x 2 + -4x = 7(x + -1) + -2 Reorder the terms: 2 + -4x = 7(-1 + x) + -2 2 + -4x = (-1 * 7 + x * 7) + -2 2 + -4x = (-7 + 7x) + -2 Reorder the terms: 2 + -4x = -7 + -2 + 7x Combine like terms: -7 + -2 = -9 2 + -4x = -9 + 7x Solving 2 + -4x = -9 + 7x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-7x' to each side of the equation. 2 + -4x + -7x = -9 + 7x + -7x Combine like terms: -4x + -7x = -11x 2 + -11x = -9 + 7x + -7x Combine like terms: 7x + -7x = 0 2 + -11x = -9 + 0 2 + -11x = -9 Add '-2' to each side of the equation. 2 + -2 + -11x = -9 + -2 Combine like terms: 2 + -2 = 0 0 + -11x = -9 + -2 -11x = -9 + -2 Combine like terms: -9 + -2 = -11 -11x = -11 Divide each side by '-11'. x = 1 Simplifying x = 1
| 14(mn)=(14m)n | | -7+x=-27 | | r-34=28 | | 3c-9=4 | | 4(-w)=3(2w+2) | | 5x+30= | | x^3-6x+3=0 | | 2(5x+8)-4(x+6)= | | 3(2x-7)+6= | | -5y+1=8y-5 | | x/4+2=x/4 | | -.3(x-4)+x=.5(6-x) | | -2ab*4bc= | | 6(x+4)/4=4x-1 | | 5(2z-5)=9(z+2)+z-43 | | 3(x+2)/5=2x-5 | | 7a+ab+5ba-3ba+a+ab= | | 2z+1/5=3z+6/5 | | 3z+1/6=4z+5/6 | | 5z+3/8=6z+7/8 | | -(3x-3)-(8x-5)+11=-5(x-1)-(9x+4)+3 | | 10(n+7)=2(35+5)n | | a+(a+4)=(a+5)-(a+1) | | y=14*-5-16 | | 8(4x-6)+x=4(4x+6)+2 | | x^2-8x-1=0 | | 4n-8=12-4n | | 17x+7=4(4x+5) | | -3.29*1.2x=6.18-9x | | -17=x+14 | | -8+4x=4+4x | | (x-4)(x^2-7x+3)= |